Plant bioindicator for detection of lead (Pb) in drinking water - Phang, Ing Chia; A Majid, Noraishah (2015)
The quality of drinking water is increasingly deteriorated as a result of anthropogenic activities. Pb contamination is frequently reported at the water sources, threatening its safety for human consumption. The application of plants as bioindicators emerges as a useful alternative to detect Pb contamination in drinking water. This study aims to search for plant that can be potentially used as a Pb bioindicator in determining water quality. In the present study, twenty-seven commonly available plant species were screened. Firstly, young leaves of plants were submerged in different concentrations of Pb solutions (0, 0.01 and 0.02 ppm). Then, morphological changes including a change in colour and shape were recorded. Comparison was made between the Pb-treated leaves and control. Among the twenty-seven plants, five plants exhibited morphological changes within 24 h of Pb treatments: Cosmos caudatus, Lactuca sativa, Piper sarmentosum, Pelargonium radula, and Plectranthus amboinicus. The observable morphological changes include browning and yellowish of leaves, as well as formation of black dots on leaves. Generally, the higher the concentration of Pb, the greater the symptoms of Pb toxicity was observed on the leaves. Severity of the Pb toxicity was also increased over time. Pb-treated Piper sarmentosum exhibited observable morphological changes at the fastest period of time, in comparison to the control. Thus, Piper sarmentosum has the potential to be used as Pb bioindicator for safety assessment of drinking water.